Out-of-hours work in cardiothoracic surgery: implications of the New Deal and Calman for training. Issue 884 (1st June 1999) - Kelty, Clive; Duffy, John; Cooper, Graham
Abstract : With the introduction of the New Deal and the Calman Report, the duration of higher specialist training will be halved. We have examined the effect of reduced on-call rotas on exposure to relatively uncommon out-of-hours emergencies in cardiothoracic surgery. Operations for post-infarction ventricular septal defect, aortic dissection or transection, oesophageal perforation and pulmonary embolus performed out-of-hours between 1990 and 1995 were identified from hospital records. Over 6 years, the period of higher specialist training in cardiothoracic surgery, a trainee would see seven aortic emergencies on a 1:2 rota, four on a 1:4 rota and two on a 1:6 rota. These figures provide a powerful argument in support of the English Clause which allows trainees to be available for 83 hours a week, equivalent to a 1:4 rota, rather than 56 hours a week, equivalent to a 1:6 rota under the New Deal. This may need supplementation by a mechanism whereby trainees are 'on call for training'.